Dopamine antagonism does not impair learning of Pavlovian conditioned approach to manipulable or non-manipulable cues but biases responding towards goal tracking - Scülfort, Stefanie; Bartsch, Dusan; Enkel, Thomas (Behavioural brain research, 2016)
Dopamine’s (DA) role in reward-processing is currently discussed as either providing a teaching signal to guide learning or mediating the transfer of incentive salience (i.e. motivational aspects) from unconditioned stimuli (US) to conditioned stimuli (CS). We used a Pavlovian conditioned approach (PCA) procedure to further investigate DAs contribution to these processes. Experiment 1 assessed the acquisition of PCA to a manipulable lever cue for 7days under DA-blockade with Flupenthixol (FLU; 225μg/kg) or Saline (SAL) treatment, followed by 6-days off-drug testing. FLU decreased the number of conditioned responses (CR) during the treatment phase, but cessation of treatment resulted in an immediate increase in CR to levels comparable to SAL controls; notably, CR in FLU-treated rats were restricted to goal tracking behaviour. During continued off-drug testing, rats from the FLU group developed sign tracking with a similar temporal pattern as controls. In experiment 2, acquisition of PCA to a non-manipulable auditory cue was investigated. FLU reduced the number of CR during treatment, and removing DA antagonism resulted in a similar rapid increase of CR as seen in experiment 1. These data complement other reports by demonstrating that, independently from the physical properties of the CS, DA is not required for learning predictive aspects of a CS-US relationship but for the development of behaviour (namely sign tracking) which is based on the motivational aspects of a CS-US relationship.